Dlaczego leśnicy nie chcą rozszerzenia Białowieskiego Parku Narodowego? Motywacja pracowników Państwowego Gospodarstwa Leśnego Lasy Państwowe w perspektywie aktorów społecznych zaangażowanych w dyskusję wokół Puszczy Białowieskiej - Niedziałkowski, Krzysztof (Leśne Prace Badawcze, 2016)
This study outlines the main motives of foresters opposing the enlargement of the Białowieża National Park to include areas managed by the State Forest Holding. The motives were identified using discourse analysis tools based on the semi-structured interviews with 36 people representing various groups of actors engaged in the discussion on the management of the Białowieża Forest. The main motives I found are connected to: (1) a vision of how nature should be and the foresters’ mission; (2) fear of losing employment or getting a worse job; (3) the high esteem of the forester profession in local communities and an inferior vocational status of the national park employees; (4) defending the professional prestige of foresters and the State Forest Holding; (5) competition with national parks over natural areas; (6) forest science; (7) the wish to continue hunting in the Białowieża Forest; (8) bottom-up pressure on the State Forest Holding employees. The major conflict potential in the discourse around the Białowieża Forest is connected with the perception of its unique natural values and methods of protection. As a result, two opposing coalitions have formed: one supporting forestry interests and one encouraging conservation. The discourse of the forestry-supporting coalition is strengthened by an epistemic community of forest scientists. Some arguments presented by the foresters pushing for a continuation of forest management in Białowieża also indicate the involvement of path dependency, which, in combination with large differences between the coalitions, does not allow for optimism regarding the resolution of the conflict.